Sosialisasi Dasar Wirausaha untuk Peningkatan Pemahaman Usaha Perseorangan bagi Siswa SMKN 1 Banyudono - Hafsah Ummu Syahidah; Triananda Nur Khairin; Refa Regita Aulia Diwanti; Muhammad Rifky Al Bukhori; Unna Ria Safitri (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This community service activity aims to improve students' understanding of entrepreneurship through the Socialization of Basic Entrepreneurship for Individual Businesses at SMKN 1 Banyudono, Boyolali Regency. Entrepreneurship education plays a crucial role in preparing vocational school students to enter the workforce and become independent entrepreneurs. However, students' understanding remains limited, both conceptually and practically, particularly regarding individual businesses. This activity was designed using a community organizing approach by actively involving students in all stages of the activity. The implementation method included entrepreneurship socialization, interactive discussions, case studies, simple business simulations, and short interviews. A mixed-method approach was used, namely qualitative through observation and discussion, and quantitative through pre-test and post-test evaluation. The results of the activity showed a significant increase in student understanding, marked by an increase in the average score from the pre-test to the post-test. In addition, there was a positive change in attitude in the form of increased participation, self-confidence, and student awareness of the potential of individual businesses as a realistic business option.